Barriers to implement lean manufacturing in Malaysian automotive industry - Mohd Azhar, Sahwan; Mohd Nizam, Ab Rahman; Baba, Md Deros (Penerbit Universiti Teknologi Malaysia, 2012)
Implementing lean manufacturing in a developing country such as Malaysia is still considered to be a major challenge due to several barriers. It is essential for all managers to understand these barriers and try to minimize them and improve competition strength. The purpose of this study is to investigate the barriers of lean manufacturing in the automotive industry in Malaysia. A survey have been conducted and sent to 250 companies from automotive manufacturing plant and suppliers in Malaysia, giving a 20.8% response rate. The statistical package for the social science (SPSS) software was used to analyze the data from the surveys. The result shows that the lack of skilled is the highest obstacle implement lean and following by lack of awareness and company culture. Attempt was made at finding significance difference between small, medium and large companies on obstacle in lean implementation. The findings of this research provide invaluable information to all desire to implement lean manufacturing and to assist the development of an effective strategic plas as well as to design programs to overcome the lean manufacturing barriers. The findings culminate with conclusion together with some proposed future research directions.